Building capacity for antiretroviral delivery in South Africa: A qualitative evaluation of the PALSA PLUS nurse training programme - Stein, J; Lewin, S; Fairall, L; Mayers, P; English, R; Bheekie, A; Bateman, E; Zwarenstein, M (BMC Health Services Research, 2008)
Abstract Background South Africa recently launched a national antiretroviral treatment programme. This has created an urgent need for nurse-training in antiretroviral treatment (ART) delivery. The PALSA PLUS programme provides guidelines and training for primary health care (PHC) nurses in the management of adult lung diseases and HIV/AIDS, including ART. A process evaluation was undertaken to document the training, explore perceptions regarding the value of the training, and compare the PALSA PLUS training approach (used at intervention sites) with the provincial training model. The evaluation was conducted alongside a randomized controlled trial measuring the effects of the PALSA PLUS nurse-training (Trial reference number ISRCTN24820584). Methods Qualitative methods were utilized, including participant observation of training sessions, focus group discussions and interviews. Data were analyzed thematically. Results Nurse uptake of PALSA PLUS training, with regard not only to ART specific components but also lung health, was high. The ongoing on-site training of all PHC nurses, as opposed to the once-off centralized training provided for ART nurses only at non-intervention clinics, enhanced nurses' experience of support for their work by allowing, not only for ongoing experiential learning, supervision and emotional support, but also for the ongoing managerial review of all those infrastructural and system-level changes required to facilitate health provider behaviour change and guideline implementation. The training of all PHC nurses in PALSA PLUS guideline use, as opposed to ART nurses only, was also perceived to better facilitate the integration of AIDS care within the clinic context. Conclusion PALSA PLUS training successfully engaged all PHC nurses in a comprehensive approach to a range of illnesses affecting both HIV positive and negative patients. PHC nurse-training for integrated systems-based interventions should be prioritized on the ART funding agenda. Training for individual provider behaviour change is nonetheless only one aspect of the ongoing system-wide interventions required to effect lasting improvements in patient care in the context of an over-burdened and under-resourced PHC system.